Microbial detoxification of mycotoxins in food - Abraham, Nadine; Chan, Edicon Tze Shun; Zhou, Ting; Seah, Stephen Y. K. (Frontiers in Microbiology, 2022)
Mycotoxins are toxic secondary metabolites produced by certain genera of fungi including but not limited to Fusarium, Aspergillus, and Penicillium. Their persistence in agricultural commodities poses a significant food safety issue owing to their carcinogenic, teratogenic, and immunosuppressive effects. Due to their inherent stability, mycotoxin levels in contaminated food often exceed the prescribed regulatory thresholds posing a risk to both humans and livestock. Although physical and chemical methods have been applied to remove mycotoxins, these approaches may reduce the nutrient quality and organoleptic properties of food. Microbial transformation of mycotoxins is promising alternative for mycotoxin detoxification as it is more specific and environmentally friendly compared to physical/chemical methods. Here we review the biological detoxification of the major mycotoxins with a focus on microbial enzymes.